Just a walk. Craandijk and the topography for the large public (Bulletin KNOB, 1989)
Renaissance topographies are written as chronicles in which landscape, architecture and historic event are used as scenery to glorify the described town or region. Also the 18th century Arcadias are not objective rendering historic events. Outlines of buildings are only vaguely sketched. Then Enlightened ideas arouse a growing national consciousness and instead of the glorifying a differentiated vision on the past. The 19th century continues the interest in the ancestor's everyday-life and by dramatizing historic events authors moreover wanted to make science accessible to the large public. Influenced by Romanticism 19th century topography uses lyrical expatiations. Just like in the 17th and 18th centuries buildings are described for their historic memories, but the knowledge of architectural aspects increases. The rise of steamboat and railways promoted tourism from 1835 on and consequently the production of guidebooks. Walks through Holland with pen and pencil (8 volumes, 1875-1888) by the clergyman Johannes Craandijk reports a walking-tour through several Dutch regions. Industrialization and the lay-out of railways forming the most important motives to write this series Craandijk wanted to record the characteristics of each region to keep alive the memory of the past and our ancestors. The described regions were selected according to his ideal of an attractive landscape and the, with this, cohering variation of line, colour and light. The glorification of these regions belongs to the Renaissance tradition and the Romantic preference for savage nature, which best can be explored wandering on foot. The history of a region and her 'natural history' provided a link with our ancestors, which aroused Craandijk many times to the description of the monuments these families lived in. His vivid and popularizing way of writing made contemporaries call him a 'historic painter'. Although just like in the Renaissance chronicles the importance of the buildings mostly has been defined by their historic value Craandijk also described buildings because of their architectural value using technical terms next to indications as line and colour (cp. landscape!) and picturesqueness. His preference for the Dutch national styles fits into the tradition of his own time; his descriptions however are not very detailed rather giving a sketch of the outlines and his impression of these buildings. This way Craandijk's Walks through Holland still is the manual for Dutch 19th century topography, a real product of his own time, but equally containing many reminiscences, as previous topographies as these are rooted in the Renaissance, the Enlightment and the Romantic tradition.